Prevalence and determinants of influenza vaccine coverage at tertiary pediatric hospitals - Newcombe, J.; Kaur, R.; Wood, N.; Seale, H.; Palasanthiran, P.; Snelling, Thomas (Elsevier, 2014)
© 2014. Despite long-standing recommendations, the uptake of influenza vaccination in children with high risk medical conditions is low. This study aimed to examine the uptake of influenza vaccination amongst a cohort of Australian children and factors associated with vaccine acceptance. Three hundred and sixteen parents of children attending outpatient clinics at the two pediatric hospitals in Sydney were recruited. The reported vaccination coverage rate was 41% among children with high risk conditions and 14% among standard risk children. There was a median of three clinic visits per high risk child at which an opportunity to vaccinate was apparently missed. Healthcare worker recommendation, having a high risk condition and parental beliefs about influenza and influenza vaccination were the most important determinants of vaccine uptake. Further studies on the beliefs and practices of doctors in this area will help guide interventions to improve vaccination rates in high risk children.